Renewable Energy Sources for Green Hydrogen Generation in Colombia and Applicable Case of Studies - Juan José Patiño; Carlos Velásquez; Edwin Ramirez; Rafael Betancur; Juan Felipe Montoya; Edwin Chica; Pablo Romero-Gómez; Arunachala Mada Kannan; Daniel Ramírez; Pedro Eusse; Franklin Jaramillo (Energies, 2023)
Electrification using renewable energy sources represents a clear path toward solving the current global energy crisis. In Colombia, this challenge also involves the diversification of the electrical energy sources to overcome the historical dependence on hydropower. In this context, green hydrogen represents a key energy carrier enabling the storage of renewable energy as well as directly powering industrial and transportation sectors. This work explores the realistic potential of the main renewable energy sources, including solar photovoltaics (8172 GW), hydropower (56 GW), wind (68 GW), and biomass (14 GW). In addition, a case study from abroad is presented, demonstrating the feasibility of using each type of renewable energy to generate green hydrogen in the country. At the end, an analysis of the most likely regions in the country and paths to deploy green hydrogen projects are presented, favoring hydropower in the short term and solar in the long run. By 2050, this energy potential will enable reaching a levelized cost of hydrogen (LCOH) of 1.7, 1.5, 3.1 and 1.4 USD/kg-H2 for solar photovoltaic, wind, hydropower and biomass, respectively.